2020
DOI: 10.1155/2020/6162802
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome and Correlation Analysis Reveal Cultivar-Specific Molecular Signatures Associated with Fruit Development and Fatty Acid Determination in Camellia oleifera Abel

Abstract: Background. Oil-tea Camellia is a very important edible oil plant widely distributed in southern China. Tea oil extracted from the oil-tea Camellia seeds is beneficial to health and is considered as a health edible oil. We attempt to identify genes related to fatty acid biosynthesis in an oil-tea Camellia seed kernel, generated a comprehensive transcriptome analysis of the seed kernel at different developmental stages, and explore optimal picking time of fruit. Material and Methods. A gas chromatography-mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…As a consequence, a study on the expression of bZIP would assist in deepening the understanding of the FA biosynthesis mechanism that is present in S. tonkinensis seeds. Glycerol-3-phosphate acyltransferase ( GPAT ) and NADPH oxidase ( NOX ) were closely associated with triacylglycerol synthesis and oleic acid metabolism, respectively [ 61 ]. We hypothesized that the FA biosynthesis process of S. tonkinensis must be regulated by numerous genes that are responsible for signal transduction, energy metabolism and so on [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a study on the expression of bZIP would assist in deepening the understanding of the FA biosynthesis mechanism that is present in S. tonkinensis seeds. Glycerol-3-phosphate acyltransferase ( GPAT ) and NADPH oxidase ( NOX ) were closely associated with triacylglycerol synthesis and oleic acid metabolism, respectively [ 61 ]. We hypothesized that the FA biosynthesis process of S. tonkinensis must be regulated by numerous genes that are responsible for signal transduction, energy metabolism and so on [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…XL27 is with 15-28 fruits per 500 g, the fresh seed rate is 50-56%, and the seed kernel oil rate is 34-37%. The detailed information about these four cultivars is available in Table 1 [2,24]. In the sampling area, the soil is red earth with organic fertilizer applied every December.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Camellia oleifera Abel., a member of the Theaceae, is an edible oil tree species of China. It is widely distributed in southern China especially in Hunan, Jiangxi and Guangxi province [1,2]. C. oleifera has a long high-yielding period (approximately one hundred years), and the secondary metabolites it produces, such as camellia seed oil, saponins, polyphenols and flavonoids, are widely used in daily life [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [36] explored the oil biosynthesis and accumulation of C. oleifera seeds at five different developmental stages. Moreover, Peng et al [37] and Lin et al [38] used RNA-seq technology to study seeds development and lipid synthesis in different C. oleifera cultivars, which provide a new insight into the lipid biosynthesis and fatty acid accumulation mechanism. Wu et al [39] conducted a comparative transcriptome study on highoil and low-oil C. oleifera cultivars and found that the high expression of SAD accelerated oleic acid synthesis and accumulation and the low expression of FAD and FAE1 decreased the consumption of oleic acid for conversion.…”
Section: Introductionmentioning
confidence: 99%